2018
DOI: 10.1108/whatt-12-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Tourism development and adaptation to climate change through legal constraint

Abstract: Purpose This paper aims to present a legal study addressing the way in which tourism development and planning in mountain areas can be adapted to climate change issues. It gives examples of attempts to regulate such development by law. Recent legislation in France has created new obligations targeted at ski resort managers. Urban planning and tourism development are key topics of the new French Mountain Act (law of 28 December 2016). The law moves back and forth between two goals, economic development and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The state of the ecological environment affects the tourism experience, and it also plays a role in limiting or boosting the speed and progress of tourism development [4]. In addition, changes in the ecological environment have strong counter-effects on tourism development, especially in terms of climate warming [5][6]. The impacts of economic and tourism development on the environment are both advantageous and disadvantageous.…”
Section: Introductionmentioning
confidence: 99%
“…The state of the ecological environment affects the tourism experience, and it also plays a role in limiting or boosting the speed and progress of tourism development [4]. In addition, changes in the ecological environment have strong counter-effects on tourism development, especially in terms of climate warming [5][6]. The impacts of economic and tourism development on the environment are both advantageous and disadvantageous.…”
Section: Introductionmentioning
confidence: 99%
“…Miller (2001) proposed an evaluation system for sustainable tourism development based on the relationship between tourism and the environment. With the deepening of research, scholars have begun to pay attention to the impacts of the ecological environment on tourism, such as the significant impacts of climate change on coastal tourism, mountaineering tourism, ice and snow tourism, etc (Shani and Arad, 2014;Joye, 2018;Vyddiyaratnam et al, 2021). Recently, some scholars have found that recreational beaches are polluted by new pollutant microplastics, which pose potential threats to the health of coastal organisms and coastal tourists (Defeo et al, 2021;Wu et al, 2021).…”
Section: Abstract Ecological Environment Tourism Development Coupling...mentioning
confidence: 99%
“…Amelung et al (2007) underscores the importance of risk assessment and the need for both limitation and adaptation. Joye (2018) highlights the role of legal constraints and the potential socio-economic and environmental implications of adaptation measures in mountain areas. Cocolas et al (2016) delve into the behavioural adaptation of winter alpine tourists, highlighting the role of tourist motivations and leisure substitutability in response to climate change impacts.…”
Section: Literature Reviewmentioning
confidence: 99%